Analisis Persepsi Masyarakat Terhadap Implementasi Smart City di Kota Gorontalo - Wunarlan, Irwan; Hatu, Ratih Ikawaty R.; Paramata, Mulyani Zahra; Abdullah, Muh. Fadli; Gobel, Sitty Faradillah Putri (Jurnal Teknik, 2024)
Over the year population have continued increase and the limited natural resources make city management increasingly complex. The concept of smart cities, which is a major issue in big cities around the world, encourages community participation. The importance of community participation in the development of technology-based public services underlies the purpose of this study to analyze community perceptions regarding the implementation of smart cities in Gorontalo City. This study uses primary data collection methods assisted by distributing questionnaires to respondents in nine sub-districts and 50 villages, as well as data obtained from institutional surveys and related documents. The results of the analysis show that the developed model is able to explain 48.26% of the variation in community perceptions of city services. It was found that positive community perceptions have the potential to increase their involvement in smart city programs, while negative perceptions can be an obstacle to implementation. This study emphasizes the importance of community understanding of the benefits of smart city technology, as well as the need for effective socialization efforts to increase community support for this initiative. The results of the analysis of community perceptions regarding the implementation of smart cities are expected to be used as a reference for local governments in formulating responsive policies to community needs.